Tallow Leaf Roller (suggested common name) Caloptilia triadicae (Davis) (Insecta: Lepidoptera: Gracillariidae) - Kristen Bowers; Andrea Lucky (EDIS)
Also published as part of the Featured Creatures collection: http://entnemdept.ufl.edu/creatures/BENEFICIAL/LEPS/Caloptilia_triadicae.html